Understanding The Driver Motivation of Women Entrepreneurs in Bandung - Cut Irna Setiawati; Titin Rini Kartini (School of Business, IPB University (SB-IPB), 2018)
In order to support the increasing number of entrepreneurs in West Java, since 2015 Dra. Mutia Oktaviana as a woman entrepreneur and Disperindag of West Java have established Product Marketing Association (APPU) West Java. This is an association which has 200 members with the composition of 180 female entrepreneurs (90%); it has potential to rise by year to year. Therefore, this research aims to know the factors which could motivate the women who are members of APPU West Java to become women entrepreneurs especially in Bandung. This research used quantitative method with descriptive and explorative research. The sample collection utilizes a technique of Nonprobability sampling and insidental sampling with 106 respondents. In addition, the data were analyzed using a factor analyzing technique which could motivate each of the entrepreneurship supporting factors. Based on the factor analyses technique using 21 factors, the results produced the formation of 7 new factors, namely family oriented, family background and friends, income stability, hobby and facility support, public existency, challenges and risks, and phisycal limitation. The most dominant factor is family oriented consisting of the following variables: running business as well as doing housework, having more time with family, creating job opportunity for family member, and the possibility of getting big profit.Keywords: women entrepreneur motivations, factor analysis, APPU